Pattern of Poisoning Cases in a Tertiary Hospital in Bangladesh (Journal of Enam Medical College, 2012)
Background: Poisoning with various substances is a global problem. It is one of the most important reasons for emergency admission in the hospital. The earlier the initial resuscitations, gastric decontamination and use of specific antidotes, the better is the outcome. Epidemiology of poisoning differs from region to region. This study was carried out to determine the pattern and severity of poisoning in a tertiary care hospital. Objective: To characterize the poisoning cases admitted in Enam Medical College Hospital. Materials and Methods: All cases admitted to the emergency department of Enam Medical College Hospital during the period of April to December, 2010 were evaluated retrospectively. We reviewed data obtained from the hospital medical records and included the following factors: demographic characteristics, etiology and outcome of the acutely poisoned patients. Total 84 poisoning cases were found and they were included in the study. Results: The overall case fatality rate was 3.5%. More detailed data from 2010 reveals that two-thirds of the patients were 20-30 years old, 53% male and 47% female. Organophosphorus was the most common cause (73.9%) followed by unknown poisoning (9.5%), sedative (5.9%), harpic (4.7%), aluminium phosphide (2.4%), savlon (1.2%), paracetamol (1.2%) and amitryptiline (1.2%). 90.5% cases were suicidal and 9.5% were homicidal. Conclusion: This study provides important information on the characteristics of the poisoning in this region. Community education about the danger of the drugs and reduction of exposure to pesticides are recommended. DOI: http://dx.doi.org/10.3329/jemc.v1i1.11133J Enam Med Col 2011; 1(1): 19-23